Effect of lead salts on phase, morphologies and photoluminescence of nanocrystalline PbMoO4 and PbWO4 synthesized by microwave radiation - Phuruangrat A. (2017)
© Wroclaw University of Technology 2016. PbMoO 4 and PbWO 4 were successfully synthesized by microwave radiation using different lead salts (acetate, chloride, nitrate and sulfate) and Na 2 MO 4 (M = Mo, W) in propylene glycol. The products were characterized by X-ray diffraction (XRD), scanning and transmission electron microscopy (SEM, TEM), Fourier transform infrared (FT-IR), Raman spectroscopy and photoluminescence (PL) spectroscopy. In this research, morphologies, crystallization and photoluminescence of the products were influenced by the kinetics of anions, including the detection of M-O (M = Mo, W) stretching modes in the (MO 4 ) 2- tetrahedrons. Photoluminescence of PbMoO 4 synthesized from Pb(NO 3 ) 2 and of PbWO 4 synthesized from PbCl 2 showed the strongest blue emission due to the electronic diffusion in tetrahedrons at room temperature.